Proceeding and papers of bank Indonesia-IMF Institute seminar on financial programming and policy. Jakarta Nopember 17 - 28 1986 - Seminar on financial programmong and policy Nopember 17-28, 1986 (Bank Indonesia, 1986)
ix, 243 p.; 24 cm.